Does being your bank’s neighbor matter? - Knyazeva, Anzhela; Knyazeva, Diana (Journal of Banking & Finance, 2012)
This paper provides new evidence on the role of distance between banks and borrowers in bank lending. We argue that delegated monitors face higher costs of collecting information about nonlocal borrowers due to the difficulty of obtaining and verifying soft information over distances. Further, the higher information collection and monitoring costs associated with distance should be reflected in loan terms. Empirically, loan spreads are increasing in the distance between borrowers and lenders. Finally, banks are more likely to include covenant provisions or require collateral when lending to borrowers located far away.